Colo-colic intussusception secondary to a giant lipoma: A case report - Karine Ibrahim, MD; Christele Lahoud, MD; Rachele Lahoud, MD; Kamal Hachem, MD; Chadi Braidy, MD (Radiology Case Reports, 2025)
Intussusception in adults is a rare condition often associated with a pathological lead point, which is frequently malignant but can occasionally be benign, such as colonic lipomas. We report the case of a 60-year-old male who presented with colicky abdominal pain, and a computed tomography (CT) revealed a colo-colic intussusception caused by a 6 cm lipoma in the transverse colon, accompanied by ischemic changes in the colonic mucosa. The patient underwent a right hemicolectomy, and histopathology confirmed the benign nature of the lesion. This case highlights the importance of early recognition and surgical intervention to prevent complications and rule out malignancy, especially in rare presentations like intussusception caused by lipomas.